Caracterização da piscicultura do tambaqui (colossoma macropomum) e dos seus efluentes na despesca: subsídios para a implementação das boas práticas de manejo da piscicultura no município de Rio Preto da Eva/AM - Martins Junior, Heitor (Instituto Nacional de Pesquisas da Amazônia - INPA, 2009)
The fish production is the activity that more grows in the Region North of Brazil; however the increment of the productive chain depends on the knowledge of the reality faced for the fish farms. The objective of this work was to characterize the fish farms of the city Rio Preto da Eva/AM, through visits and application of questionnaires, with also validating the use of the BPM to minimize the impacts of the launching of the draining water during the for take off the fish. Tambaqui (Colossoma macropomum) is the more cultivated fish. The results evidence that the fish farms in the city counts on two heterogeneous types of producers, which possess distinct conditions of insertion in its respective markets. Of a side, some fish farms can be fit as producing capitalized that carry through significant investments in the production and objectify the commercialization, however these are minority. The great majority has minor‟s investments in the production and technology and if they characterize for the fish farms that search an income alternative. The adoption of the BPM in part of the excavated fisheries had had positive effect on the quality of the effluent, as well the use of the taxes of draining between 50 and 75% at the moment take off the fish. The variable: oxygen dissolved DBO5, Chlorophyll a, settle able matter and total phosphorus, at some moment had exceeded the limit established by the CONAMA. However the handling of the taxes of draining for takeoff the fish, can keep the adequate levels of dissolved oxygen, DQO and Chlorophyll-a, but it does not stop texts of the settle able matter and total phosphorus.
Keywords: Manejo do Tambaqui; Piscicultura